1979
DOI: 10.1128/aem.37.4.725-728.1979
|View full text |Cite
|
Sign up to set email alerts
|

Secondary selective enrichment of salmonellae from naturally contaminated specimens by using a selective motility system

Abstract: A selective motility medium was used as a secondary selective enrichment medium to examine specimens naturally contaminated with salmonellae. The medium, incubated at 37°C, was inoculated from either selenite brilliant green sulfa enrichment broth or Muller-Kauffman tetrathionate broth, both of which had been incubated at 42°C. The use of the selective motility medium resulted in an increase in the number of positive specimens from 65 and 74% to 80 and 82%, when inoculated at 24 and 48 h, respectively, from te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In the examination of 454 samples of meat products, we found that, after preenrichment, the use of an enrichment in MK broth, incubated at 430C for 2 days, 92 specimens were found to be positive for salmonellae, whereas with a secondary enrichment in SMM made from the MK broth, 121 samples were found to be positive (P < 0.05). Thus, we were able to confirm the observations of Smeltzer and Dulcalfe (7). However, after preenrichment, the simple enrichment in 10 ml of RV broth at 430C for 1 day yielded 149 positive specimens, instead of 121 positive specimens found after secondary enrichment in SMM (P -0.05) and 92 positive specimens detected by MK broth (P < 0.001) ( Table 1).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the examination of 454 samples of meat products, we found that, after preenrichment, the use of an enrichment in MK broth, incubated at 430C for 2 days, 92 specimens were found to be positive for salmonellae, whereas with a secondary enrichment in SMM made from the MK broth, 121 samples were found to be positive (P < 0.05). Thus, we were able to confirm the observations of Smeltzer and Dulcalfe (7). However, after preenrichment, the simple enrichment in 10 ml of RV broth at 430C for 1 day yielded 149 positive specimens, instead of 121 positive specimens found after secondary enrichment in SMM (P -0.05) and 92 positive specimens detected by MK broth (P < 0.001) ( Table 1).…”
Section: Resultssupporting
confidence: 86%
“…There is now a tendency to utilize preenrichment, followed by enrichment, in the isolation of salmonellae from food and water (1,4,7,8,10). In addition to the fluid enrichment procedures in use, motility media may be employed both for primary enrichment (2) and secondary enrichment (3,7).…”
mentioning
confidence: 99%
“…The recovery of Salmonella from various specimens with a variety of media and incubation conditions has been documented (1,3,(5)(6)(7)(9)(10)(11)(12)(13)(14). Recently, the efficacies of several new selective media for the isolation of Salmonella have been compared.…”
mentioning
confidence: 99%
“…The selective motility test has been recoynended both as primary enrichment (Stuart and Pivnick 1965;Harper and Shortridge 1969;Chau and Huang 1976;Svastova et al 1984) and as secondary enrichment (Harvey et al 1966;Price 1979, 1982;Smeltzer and Duncalfe 1979). Smeltzer and Duncalfe (1979) described the use of the selective motility medium of Harper and Shortridge ( 1969) as a secondary selective enrichment medium to increase the isolation rate of salmonellae. Use of this medium resulted in an increase in the number of positive specimens from 65 and 74% to 80 and 82% when inoculated at 24 and 48 h, respectively, from Muller-Kauffman tetrathionate broth.…”
Section: Semisolid Selective Motility Media For Salmonellamentioning
confidence: 99%